Peramalan Jumlah Penumpang Datang Melalui Transportasi Udara Di Sulawesi Tengah Menggunakan Support Vector Regression (SVR) - Purnama, D I (Program Studi Matematika, Universitas Tadulako, 2020)
The number of air transportation passengers in Central Sulawesi shows an increase and decrease every month. For this reason, a forecasting method is needed to predict the number of air transportation passengers in the future. Because the pattern of data on the number of air transportation passengers in Central Sulawesi Province has a nonlinear data pattern, a forecasting method is needed that can overcome these problems where in this study using the SVR model. In this study, the SVR model uses the RBF kernel function to overcome nonlinear data patterns and uses the grid search method to obtain the optimal parameters of the model.